Prevalence and clinical characteristics of fulminant type 1 diabetes mellitus in Korean adults: A multi‐institutional joint research. Issue 1 (31st August 2021) - Song, Sun Ok; Yun, Jae‐Seung; Ko, Seung‐Hyun; Ahn, Yu‐Bae; Kim, Bo‐Yeon; Kim, Chul‐Hee; Jeon, Ja Young; Kim, Dae Jung; Seo, Da Hae; Kim, So Hun; Noh, Jung Hyun; Lee, Da Young; et al.
Abstract: Aims/Introduction: We aimed to determine the hospital‐based prevalence and clinical features of fulminant type 1 diabetes mellitus in Korea. Materials and Methods: We identified all patients with diabetes who regularly visited the Endocrinology outpatient clinics at eight centers for a period >1 year between January 2012 and June 2017. We investigated their medical records retrospectively. Results: During this period, 76, 309 patients with diabetes had been regularly followed up. Among them, 913 (1.2%) patients had type 1 diabetes mellitus . There were 462 patients with type 1 diabetes mellitus whose data at the time of the first diagnosis could be identified (359 and 103 with non‐ketosis and ketosis onset, respectively). Of these, 15 (3.2% of type 1 diabetes mellitus, 14.6% of ketosis onset diabetes) patients had fulminant type 1 diabetes mellitus. The median ages at diagnosis were 40 and 27 years in the fulminant type 1 diabetes mellitus and non‐fulminant type 1 diabetes mellitus groups, respectively. The patients with fulminant type 1 diabetes mellitus had higher body mass index, lower glycated hemoglobin and fasting/peak C‐peptide, and lower frequent glutamic acid decarboxylase antibody‐positive rate ( P =0.0010) at diagnosis. Furthermore, they had lower glycated hemoglobin at the last follow‐up examination than those with non‐fulminant type 1 diabetes mellitus. Conclusions: In this study, the prevalence of type 1 diabetes mellitus was 1.2% among all patients with diabetes, and that of fulminant type 1 diabetes mellitus was 3.2% among those newly diagnosed with type 1 diabetes mellitus. The glycated hemoglobin levels were lower in patients with fulminant type 1 diabetes mellitus than in those with non‐fulminant type 1 diabetes mellitus at diagnosis and at the last follow‐up examination. Abstract : We provide novel information on the prevalence and clinical features of fulminant type 1 diabetes mellitus in Korea.